Best Practices in Manufacturing Processes Experiences from Latin America - García Alcaraz, Jorge Luis.; Rivera Cadavid, Leonardo; González-Ramírez, Rosa Guadalupe; Leal Jamil, George; Chong Chong, Mario Gustavo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports the best practices that companies established in Latin America are implementing in their manufacturing processes in order to generate high quality products and stay in the market. It lists the technologies, production and administrative philosophies that are being implemented, presenting a collection of successful cases of studies from Latin America. The book describes how the tools and techniques are being integrated, modified and combined to create new technical resources for assisting the decision making process for better economic performance in manufacturing companies. The efforts deployed for assisting the transformation of raw materials into products and services are described. The authors explain the main key success factors or drivers for success of each tool, technique or hybrid combination approach applied to solve manufacturing problems. .
Techniques, Tools and Methologies -- Production management -- Manufacturing and Technology -- Human factors.
Keywords: Manufactures; Operations research; Industrial Management; Machines, Tools, Processes; Operations Research and Decision Theory; Industrial Management